Bacterial Human Virulence Genes across Diverse Habitats As Assessed by In silico Analysis of Environmental Metagenomes - Søborg, Ditte A.; Hendriksen, Niels B.; Kilian, Mogens; Christensen, Jan H.; Kroer, Niels (Frontiers in Microbiology, 2016)
The occurrence and distribution of clinically relevant bacterial virulence genes across natural (non-human) environments is not well understood. We aimed to investigate the occurrence of homologues to bacterial human virulence genes in a variety of ecological niches to better understand the role of natural environments in the evolution of bacterial virulence. Twentyfour bacterial virulence genes were analyzed in 47 diverse environmental metagenomic datasets, representing various soils, seawater, freshwater, marine sediments, hot springs, the deep-sea, hypersaline mats, microbialites, gutless worms and glacial ice. Homologues to 17 bacterial human virulence genes, involved in urinary tract infections, gastrointestinal diseases, skin diseases, and wound and systemic infections, showed global ubiquity. A principal component analysis did not demonstrate clear trends across the metagenomes with respect to occurrence and frequency of observed gene homologues. Full-length (>95%) homologues of several virulence genes were identified, and translated sequences of the environmental and clinical genes were up to 50-100% identical. Furthermore, phylogenetic analyses indicated deep branching positions of some of the environmental gene homologues, suggesting that they represent ancient lineages in the phylogeny of the clinical genes. Fifteen virulence gene homologues were detected in metagenomes based on metatranscriptomic data, providing evidence of environmental expression. The ubiquitous presence and transcription of the virulence gene homologues in non-human environments point to an important ecological role of the genes for the activity and survival of environmental bacteria. Furthermore, the high degree of sequence conservation between several of the environmental and clinical genes suggests common ancestral origins.